Turbokapitalizm – szanse i zagrożenia rozwoju w warunkach gospodarki wysoko rozwiniętej - Brudnicki, Piotr (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2013)
This paper acquainted readers with the concept of turbo-capitalism as a form of capitalism. The person who precisely defi ne this is Edward Luttwak, term of turbo-capitalism through free markets, privatization, globalization and deregulation. The paper set the basic differences between capitalism and turbo-capitalism. Economic stability and job security is for the individual “better tomorrow”. The development of technology and faster flow of information should promote economic development and economic progress of modern states. I would like to draw. the attention on the fact that turbo-capitalism is focused on maximizing profits, which does not solve social problems. National governments are losing economic strenght and, consequently, reduces social welfare and does not prevent crime and terrorism. Multiplication of turbo-capitalism profits leads to the increase of unemployment and therefore social pathology. This paper shows that the wellbeing, which is the main objective of turbo-capitalism, could not be the main goal of politics and society as it improves the material status of a few individuals, while it does not bring happiness to the majority. My work in this area is a “voice” of the wise limitations of turbo-capitalism, because this process uncontrolled can lead to the destruction of mankind. I tried to show that turbo-capitalism is the greatest threat to democracy. Capitalism could not focus on the individual, because it leads to “loneliness” of people in a wide range. In my work I have acquainted the reader with the situation created in Bhutan, during the inventions of civilization. I had presented in this work opportunities for Third World countries through the free movement of capital, modern technologies and investments. The reader has to understand, however, that the information revolution brings very big threat to humanity. The Industrial Revolution leads t o rapid growth in employment and decline of information technology indicators at one time. The reader should learn from the negative effects of the American turbo-capitalism and help to develop positive qualities.